THE INFLUENCE OF WORK ETHICS ON EMPLOYEE PERFORMANCE WITH WORK CULTURE AS A MODERATING VARIABLE - Dean Seshar Rahmadina; Suratman; Fitria Damayanti; Denny Rakhmad Widi Ashari; Urip Triandri (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main supporting tool for building argumentative constructs in this study. The data used in this article are primary data that researchers obtained from 400 Bank Mandiri employees spread throughout Indonesia. Data obtained from 400 Bank Mandiri employees spread throughout Indonesia. The data were analyzed using the smart PLS 4.0 analysis tool.